2019
DOI: 10.3168/jds.2018-15601
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolite changes in dairy cows during parturition identified using untargeted metabolomics

Abstract: The metabolic responses of cows undergo substantial changes during the transition from late pregnancy to early lactation. However, the molecular mechanisms associated with these changes in physiological metabolism have not been clearly elucidated. The objective of this study was to investigate metabolic changes in transition cows from the perspective of plasma metabolites. Plasma samples collected from 24 multiparous dairy cows on approximately d 21 prepartum and immediately postpartum were analyzed using ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 59 publications
10
40
1
Order By: Relevance
“…However, animals differ tremendously in their adaptive success [51]. Results from HC group versus PHC group showed that the DEGs were primarily involved in ion homeostasis, fat digestion, and lipid metabolism; this is a finding that is similar to what has been reported using metabolomic analysis in transition cows [52]. Otherwise, the inflammation-related pathways of "IL-17 signaling pathway" and "NOD-like receptor signaling pathway" were obtained.…”
Section: Discussionsupporting
confidence: 78%
“…However, animals differ tremendously in their adaptive success [51]. Results from HC group versus PHC group showed that the DEGs were primarily involved in ion homeostasis, fat digestion, and lipid metabolism; this is a finding that is similar to what has been reported using metabolomic analysis in transition cows [52]. Otherwise, the inflammation-related pathways of "IL-17 signaling pathway" and "NOD-like receptor signaling pathway" were obtained.…”
Section: Discussionsupporting
confidence: 78%
“…These metabolites were found to be significantly enriched in arginine and proline metabolism, while these proteins were mainly enriched into biological processes and pathways associated with cholesterol metabolism and phagosome. This finding is consistent with a previous study that showed that amino acid metabolism and energy metabolism are related changes in transition cows (Luo et al, 2019). Nevertheless, it should be noted that we did not demonstrate the inflammation-related pathways as we have previously shown from transcriptome data with the same animals.…”
Section: Discussionsupporting
confidence: 93%
“…The LC-MS based metabolomic analysis has been described previously (Dunn et al, 2011;Luo et al, 2019). In brief, all 38 serum samples were slowly thawed at 4 • C, and 100 µl of serum was mixed with 400 µl pre-cooled methanol.…”
Section: Liquid Chromatography Mass Spectrometry Metabolomics Analysismentioning
confidence: 99%
“…Prostaglandin E 2 (PGE 2 ) significantly decreases in the blood of LDA dairy cows [1], but leukotriene D4 (LTD 4 ) has not been investigated. PGE 2 and LTD 4 are derived from arachidonic acid via the cyclooxygenase/lipoxygenase pathway [29]. PGE 2 can regulate the gastrointestinal integrity, fertility and the inflammatory response [20], and LTD 4 can act as a regulator of leukocyte chemotaxis, the inflammatory response and the contraction of gastrointestinal smooth muscle [31].…”
Section: Discussionmentioning
confidence: 99%
“…During gluconeogenesis and ketogenesis, NH 3 obtained from the deamination of amino acids is used to generate carbamoyl phosphate, and this product can be decomposed into citrulline and pyrimidine. Certain amino acids involved in the urea cycle, such as proline, ornithine arginine and citrulline, have been confirmed to participate in the TCA cycle by affecting the formation of fumarate [29,41]. Pyrimidine is used to synthesize uridine, which can be phosphorylated to produce uridine triphosphate.…”
Section: Discussionmentioning
confidence: 99%